La disparition progressive et programmée de la gestion des passions politiques - Enriquez, Eugène (História: Questões & Debates, 2022)
In this article, we contextualize the theme of political passions in the field of Sociology, noting that they are currently undergoing a period of appeasement. First, because society has been overtaken by the fad of “political correctness”. Secondly, because emotions have been diverted elsewhere, that is, to social networks, whose verbal violence aims, consciously or not, to provoke another type of passion, of the sort that attempts to destroy specific individuals and communities.